Phytase in diets with crude protein levels for commercial layers - Adriana Aparecida Pereira; Otto Mack Junqueira; Dirceu Neutzling Griep Junior; Dorgival Morais de Lima Júnior; Sarah Sgavioli; Socorro Morais (Acta Scientiarum. Animal Sciences, 2017)
The aim of this study was to evaluate the action of the phytase enzyme in diets formulated with variations in the crude protein content on performance and egg quality of commercial layers. A total of 336 commercial layers were housed at eight birds per cage in a 3 × 2 factorial arrangement with seven replicates. Treatments consisted of four crude-protein levels (17, 15, and 13%) and two enzyme levels (0 and 500 FTU kg-1 diet), distributed in a completely randomized design. Feed intake, egg production, feed conversion per dozen eggs and per kilogram, egg weight and mass, specific gravity, eggshell thickness, and Haugh unit were measured over five 28-day periods. The performance of commercial layers fed the diet containing 13% crude protein worsened, irrespective of phytase addition. However, at 15% crude protein, phytase inclusion did not affect feed conversion or egg weight. Inclusion of phytase leads to equal egg-quality and performance results at the dietary crude protein levels of 17 and 15%. The crude protein content of 13%, with or without phytase, is not recommended for the diet of brown-egg layers.